Hubungan Antara Sosiodemografi dengan Kualitas Hidup pada Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis di RSUD Welas Asih - Aulia Namira Nur Febriyanti; Theresia Eriyani; Maria Komariah (Universitas Malahayati Lampung, 2026)
ABSTRACT Long-term hemodialysis (HD) treatment can influence the quality of life of individuals with chronic kidney disease (CKD). The quality of life among CKD patients receiving HD is affected by multiple determinants, including sociodemographic characteristics. This study was conducted to examine the association between age, sex, and level of education and the quality of life of patients undergoing hemodialysis at RSUD Welas Asih in September–October 2024. A quantitative approach with Secondary Data Analysis was applied using a dataset from a research project conducted by the Faculty of Nursing, Universitas Padjadjaran entitled “Harmony in Health: The Intersection of Natural Resources and Well-Being.” Sample selection was conducted using nonprobability sampling techniques through a purposive approach to secondary data. The WHOQOL-BREF questionnaire served as the measurement instrument. Data analysis included univariate and bivariate procedures, with the Chi-Square test used for statistical analysis. The findings indicated that the majority of respondents demonstrated a good quality of life (85.7%). More than half of the participants reported satisfactory health perceptions (54.3%), while 43.8% reported a positive perception of overall quality of life. Bivariate testing revealed no statistically significant relationship between age or educational level and quality of life. In contrast, a significant association was found between gender and quality of life (p = 0.027), with female patients experiencing more varied and complex physical and psychosocial conditions. The results highlight the need for comprehensive patient management that acknowledges sociodemographic variations, especially gender differences, and incorporates physical, psychological, social, and environmental dimensions in order to enhance the quality of life of patients. Keywords: Hemodialysis, Quality of Life, Sociodemographic, Chronic Kidney Disease ABSTRAK Terapi hemodialisis yang dijalani dalam jangka waktu lama dapat berdampak pada kualitas hidup pasien dengan penyakit ginjal kronis (PGK). Kualitas hidup pasien PGK yang menjalani HD dipengaruhi oleh berbagai determinan, salah satunya adalah karakteristik sosiodemografi. Penelitian ini bertujuan untuk mengkaji hubungan antara umur, gender, dan tingkat pendidikan dengan kualitas hidup pasien PGK yang menjalani hemodialisis di RSUD Welas Asih pada periode September–Oktober 2024. Penelitian menggunakan desain kuantitatif dengan pendekatan analisis data sekunder yang berasal dari dataset penelitian dosen Fakultas Keperawatan Universitas Padjadjaran berjudul “Harmony in Health: The Intersection of Natural Resources and Well Being.” Pemilihan sampel dilakukan menggunakan teknik nonprobability sampling melalui pendekatan purposive terhadap data sekunder. Instrumen pengumpulan data menggunakan kuesioner WHOQOL-BREF. Analisis data dilakukan secara univariat dan bivariat dengan uji statistik Chi-Square. Hasil penelitian menunjukkan bahwa mayoritas responden memiliki kualitas kesejahteraan hidup dalam kategori baik (85,7%), dengan persepsi kesehatan yang memuaskan (54,3%) serta persepsi kualitas kesejahteraan hidup secara umum yang baik (43,8%). Analisis bivariat menunjukkan tidak terdapat hubungan antara usia maupun tingkat pendidikan dengan kualitas hidup. Sebaliknya, terdapat hubungan antara jenis kelamin dengan kualitas hidup (p = 0,027), dengan pasien perempuan menunjukkan pengalaman fisik dan psikososial yang lebih beragam dan kompleks. Temuan menegaskan perlunya layanan kesehatan yang komprehensif untuk meningkatkan kualitas kesejahteraan hidup pasien, dengan mempertimbangkan perbedaan karakteristik sosiodemografi, khususnya gender, serta mencakup aspek fisik, psikologis, sosial, dan lingkungan. Kata Kunci: Kualitas Hidup, Penyakit Ginjal Kronis, Sosiodemografi, Hemodialisis.